2017
DOI: 10.1186/s13017-017-0143-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following repair of incarcerated and strangulated ventral hernias with or without synthetic mesh

Abstract: BackgroundThe use of synthetic mesh for ventral hernia repair under contaminated conditions is a controversial issue due to the considerable risk of surgical site infection (SSI). This study aimed to review the outcomes of repair of incarcerated and strangulated ventral hernias with or without synthetic mesh in compliance with established clinical guidelines regarding the incidence of SSI and hernia recurrence.MethodsThe records of patients with complicated ventral hernias who were treated with or without synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 28 publications
6
36
0
Order By: Relevance
“…This is followed, simultaneously by divarication of recti and abdominal wound dehiscence, each accounting for less than a tenth (8.8%) of the reconstructions done ( Table 2 ). These findings are similar to previous results from Nigeria, South Korea, Yemen, Europe and Saudi Arabia [ 1 , 13 , 16 - 18 , 22 - 24 ]. Majority (68.1%) of our patients reported that cosmetic correction is the primary reason they sought reconstruction, followed by abdominal pain (12.1%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is followed, simultaneously by divarication of recti and abdominal wound dehiscence, each accounting for less than a tenth (8.8%) of the reconstructions done ( Table 2 ). These findings are similar to previous results from Nigeria, South Korea, Yemen, Europe and Saudi Arabia [ 1 , 13 , 16 - 18 , 22 - 24 ]. Majority (68.1%) of our patients reported that cosmetic correction is the primary reason they sought reconstruction, followed by abdominal pain (12.1%).…”
Section: Discussionsupporting
confidence: 92%
“…Majority (68.1%) of our patients reported that cosmetic correction is the primary reason they sought reconstruction, followed by abdominal pain (12.1%). This is comparable to results from Saudi Arabia where 63.4% of the patients stated cosmetics as their major reason for seeking repair, followed by abdominal pain (24.1%) [ 24 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, they also found that the most frequently used method of open repair was plug repair, which was performed in 894 procedures, followed by the McVay repair (n = 186), which often resulted in increased recurrence. Lost to follow-up 2 (3.9) 4 (7.5) All the different recurrence rates were significantly correlated with surgical status (emergency or elective), repair methods (laparoscopic repair, OPR or OSR), and the surgeon's experience 2,9,14,16 . The focus of this study was open repair for emergency FHs, so the overall recurrence rate might be higher.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reports have been reported in the literature 10 . Seroma is a common complication after emergency hernia repair 9 . UHS 22 mesh was selected for OPR of FHs due to its bilayer polypropylene structure; another important reason for this approach was that the material of the UHS mesh is made of an absorbable polycarbon-25 coating and nonabsorbent polypropylene filament fibres that have antimicrobial properties 23 .…”
Section: Discussionmentioning
confidence: 99%